Dataset on antioxidant metabolites and enzymes activities of freshly harvested sweet cherries (Prunus avium L.) of Campania accessions - Mirto, Antonio (Data Brief, 2017)
In this article, we reported the original data obtained by the study of metabolites and enzymes involved in sweet cherry antioxidant system. We measured hydrogen peroxide (H(2)O(2)) and malondialdehyde (MDA), which are indicator of oxidative stress. Moreover, we measured the concentration of reduced and oxidized ascorbate and glutathione that are involved in ROS detoxification together with phenolics, anthocyanins and tocopherols. Among antioxidant enzymes, we analyzed the activities of ascorbate peroxidase (APX; EC 1.11.1.11), and the soluble and bound forms of polyphenol oxidase (PPO; EC 1.10.3.1) and guaiacol peroxidase (POD; EC 1.11.1.7). The data reported in this paper are related to the research article “Metabolic characterization and antioxidant activity in sweet cherry (Prunus avium L.) Campania accessions”, authored by Mirto et al. (2018) [1].